Accuracy of Radiological Features for Predicting Extracorporeal Shock Wave Lithotripsy Success for Treatment of Kidney Calculi - Arshadi, Hamid; Dianat, Seyed Saied; Ganjehei, Leila (Urology Journal, 2009)
Introduction: Our aim was to assess the accuracy of radiological characteristics observed by the urologist in estimating the success rate of extracorporeal shock wave lithotripsy (SWL) in patients with kidney calculi. Materials and Methods: Patients with kidney calculi sized 10 mm to 15 mm who underwent SWL in our center were enrolled. One urologist estimated the success chance of SWL based on plain abdominal radiography. Accordingly, the patients were categorized into 2 groups with more than 75% chance of fragmentation (group 1) and with 50% to 75% estimated chance of fragmentation (group 2). Factors used for estimation included calculus shape, homogeneity, and density as compared with the adjacent 12th rib. The estimations were compared with the resulted stone-free rate after a 3-month follow-up. Results: A total of 137 patients were studied, of whom, 92 (67.2%) were categorized in group 1 and 45 (32.8%) in group 2, before the lithotripsy. Successful treatment was recorded in 101 patients (73.7%). Eighty-five patients with favorable estimated chance of successful lithotripsy (92.4%) had successful SWL, and 29 with less favorable estimate (64.4%) did not have successful fragmentation following 2 sessions of SWL (P < .001). The sensitivity and specificity of radiological parameters for prediction of treatment success were 84.2% and 80.6%, respectively. Conclusion: We found that certain radiographic features of urinary calculi such as calculus density, as compared with the adjacent bone, and calculus shape could have predictive impression for the success rate of SWL.